Rancang Bangun Alat Hand Sanitizer Otomatis dan Pengukur Suhu Tubuh - Rouhillah; Inzar Salfikar; Hafis Husna (J-Innovation, 2024)
During the Covid-19 pandemic, medical equipment is needed by all humans. One of them that is widely used as initial protection is hand sanitizer. Hand sanitizer is an antiseptic in the form of a gel that is widely used as a practical hand sanitizer. This final project aims to make a body temperature checking device and automatic hand sanitizer spraying, so that with this tool it can help prevent the transmission of the Covid-19 virus in routinely checking body temperature and cleaning hands from bacteria or germs without touching the tool. The sensors used in the manufacture of this final project consist of a temperature sensor mlx90614 as a body temperature detector and a proximity sensor as a trigger for a water pump. LCD (Liquid Crystal Display) serves to display temperature data that has been detected and the speaker emits sound according to the temperature detected later. Based on the detection accurasy test, the accurasy value is 94,74%.